(2Z)-3-Hydroxy-3-(4-R-Phenyl)-Prop-2-Enedithioic Acids as New Antituberculosis Compounds - Pretelín-Castillo G; Silva Miranda M; Espitia C; Chávez-Santos RM; Suárez-Castro A; Chacón-García L; Aguayo-Ortiz R; Martinez R (Infection and Drug Resistance, 2021)
Gustavo Pretelín-Castillo,1 Mayra Silva Miranda,2,3 Clara Espitia,2,3 Rosa María Chávez-Santos,1 Abel Suárez-Castro,4 Luis Chacón-García,4 Rodrigo Aguayo-Ortiz,5 Roberto Martinez1 1Instituto de Química, Universidad Nacional Autónoma de México, Circuito Exterior, Ciudad Universitaria, Cd. México, 04510, México; 2Catedrática CONACYT adscrita al Instituto de Investigaciones Biomédicas, Universidad Nacional Autónoma de México, Ciudad Universitaria, Cd. México, 04510, México; 3Instituto de Investigaciones Biomédicas, Universidad Nacional Autónoma de México, Departamento de Inmunología, Ciudad Universitaria, Cd. México, 04510, México; 4Instituto de Investigaciones Químico-Biológicas, Universidad Michoacana de San Nicolás de Hidalgo, Edificio B-1, Ciudad Universitaria, Morelia Michoacán, 58030, México; 5Departamento de Farmacia, Facultad de Química, Universidad Nacional Autónoma de México, Circuito Exterior, Ciudad Universitaria, Cd. México, 04510, MéxicoCorrespondence: Roberto MartinezInstituto de Química, Universidad Nacional Autónoma de México, Circuito Exterior, Ciudad Universitaria, Cd. México, 04510, MéxicoTel +52 55 56224441Fax +52 55 56162217Email robmar@unam.mxBackground: Tuberculosis is an infectious disease caused by the bacillus Mycobacterium tuberculosis. Compounds including a sulfur-containing scaffold have been shown to be key scaffolds in various antituberculosis agents. Interestingly, the 3-hydroxy-3-phenyl-prop-2-enedithioic acids 11a-j have, to the best of our knowledge, not been previously described as antituberculosis agents.Purpose: In the present study, we investigated the role of substituents attached to the phenyl ring of a 3-hydroxy-3-phenyl-prop-2-enedithioic acid scaffold (compounds 11a–j) in inhibiting the growth of M. tuberculosis strain H37Rv.Methods: (Z)-3-hydroxy-3-(4-R-phenyl)-prop-2-enedithioic acids 11b–j, with R groups including various electron-donating or electron-withdrawing groups, were designed by structurally modifying the lead compound 11a. The syntheses of 11a–j involved each one-step procedure starting from the corresponding substituted acetophenone. Compounds 11a–j were tested against M. tuberculosis strain H37Rv to evaluate their bacterial growth inhibitory activities. ADMET profiles were predicted by employing three different methods. In addition, molecular docking studies were carried out, based on the molecular similarities of the synthesized compounds with ethionamide ( 5), on the active site of the M. tuberculosis H37Rv (3R)-hydroxyacyl-ACP (HadAB) dehydratase heterodimer.Results: The antituberculosis activities of compounds 11a–j could be explained in terms of the presence of electron-donating or electron-withdrawing substituents on the aromatic ring of the substituted 3-hydroxy-3-phenyl)-prop-2-enedithioic acid core. The activity and selectivity index (SI) value of (Z)-3-hydroxy-3-(4-nitrophenyl)-prop-2-enedithioic acid 11e suggested that this compound could be used for the design of novel antituberculosis agents. Most of the synthesized molecules showed an acceptable ADME profile and a low probability of being toxic. Docking studies of 11d and 11e showed them forming hydrogen bonds with the ACys61 residue of the HadAB enzyme.Conclusion: Our results suggested that the antituberculosis compound 11e could be used for the design of novel antituberculosis agents.Keywords: synthesis, 3-hydroxy-3-(4-R-phenyl)-prop-2-enedithioic acids, antituberculosis agents, docking, theoretical ADME